A REVIEW ON USAGE OF NANO-PARTICLES IN NUCLEAR POWER PLANTS - Bandhu, Din; Kumar, Ritesh (International Journal of Research -GRANTHAALAYAH, 2017)
Nuclear power plants are big in construction and possess complex facilities. These plants usually operate at very large temperatures and the materials used in their construction experience considerably higher levels of radiation. It is therefore very important to understand the effects of radiation on these materials. Radiation is responsible for defects which affects the strength and performance of the materials. In this review paper, we have suggested one idea for constructing an efficient nuclear power plant by using nano-particles. This paper also details about nano-particles in an elaborated way and a few of them can be used for constructing nuclear power plants (NPP).